2016
DOI: 10.1016/j.joca.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profile implicates potential cartilage regeneration at the late stage of knee osteoarthritis

Abstract: Our data suggested the changes in DNA methylation occurred at the late stage of OA. Pathways and networks enriched in identified DM genes highlighted potential etiologic mechanism and implicated the potential cartilage regeneration in the late stage of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…Our data indicates that where there was previously no evidence of methylation changes in gene promoters during OA, such as ACAN and p21WAF1/CIPl, that dynamic methylation at enhancers regulating such genes should be considered (Poschl et al , 2005; Sesselmann et al , 2009). A number of studies have also identified DNA methylation changes in OA or damaged cartilage but it remains to be determined whether these correspond to enhancer regions (den Hollander et al , 2014; Fernandez-Tajes et al , 2014; Jeffries et al , 2014; Alvarez-Garcia et al , 2016; Bonin et al , 2016; Zhang et al , 2016; Steinberg et al , 2017). The subset of chondrogenesis DMLs also significantly altered in OA become hypomethylated consistent with the cells reactivating developmental pathways (Loeser et al , 2012; Reynard, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicates that where there was previously no evidence of methylation changes in gene promoters during OA, such as ACAN and p21WAF1/CIPl, that dynamic methylation at enhancers regulating such genes should be considered (Poschl et al , 2005; Sesselmann et al , 2009). A number of studies have also identified DNA methylation changes in OA or damaged cartilage but it remains to be determined whether these correspond to enhancer regions (den Hollander et al , 2014; Fernandez-Tajes et al , 2014; Jeffries et al , 2014; Alvarez-Garcia et al , 2016; Bonin et al , 2016; Zhang et al , 2016; Steinberg et al , 2017). The subset of chondrogenesis DMLs also significantly altered in OA become hypomethylated consistent with the cells reactivating developmental pathways (Loeser et al , 2012; Reynard, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant DNA methylation in enhancers has been implicated in diseases such as cancer [44][45][46] and osteoarthritis (OA) [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation levels of some CpG sites on OA cartilage were correlated with the histopathologic disease severity score, assessed by modified Mankin score (Jeffries et al 2014). Recently, Zhang et al reported changes in DNA methylation profile of OA chondrocytes according to disease progression, with changes preferentially observed at last stage of OA (Zhang et al 2016). …”
Section: Epigenetics and Musculoskeletal Function During Agingmentioning
confidence: 99%